The Australian high performance and sport science workforce: A national profile - Dwyer, D. B.; Bellesini, K.; Gastin, P.; Kremer, P.; Dawson, A. (Journal of Science and Medicine in Sport, 2019)
Objectives: The purpose of this study was to provide a profile of the demographics and employment characteristics of the Australian high performance and sport science workforce. Design: This study used a cross-sectional, quantitative survey methodology to collect data about the Australian high performance and sport science workforce. Method: 175 Australian high performance and sport science employees completed an online survey which captured demographic information and work-related characteristics such as role, industry sector, income, permanence of employment and hours worked. Descriptive statistics were used to summarise information and some comparisons were made between position titles, industry sectors and sexes. Results: The Australian high performance and sport science workforce is predominantly male (76.0%), =35 years of age (50.3%), located on the eastern seaboard of Australia (69%) and have been in their current position for 2-5 years (37.4%). They are mostly employed on a fixed term contract of 2.4 years, by an institute of sport. Income varied, with those working in professional sporting clubs and/or employed as high performance managers earning the highest wage. On average, participants worked well over their contracted hours, with a considerable proportion of these hours outside the standard 9-5 working week. Conclusions: Employees in the high performance and sport science workforce in Australia face significant professional issues that relate to long and unusual work hours, job insecurity and income disparity. Policy makers and the managers of this workforce should consider the impact of these issues on work-life balance, staff retention rates and the risk of burnout. ABSTRACT FROM AUTHOR